From eviction to empowerment: How beekeeping helps Ogiek youth reclaim their agency and land rights in Kenya - Nyang’ori Ohenjo; Amina Yusuf Maalim (2025)
Kibet’s story of survival and innovation is a symbol of hope. It shows how beekeeping has enabled the youth in his community in Kenya to revitalize their indigenous knowledge to build climate change resilience and improve their food security. The Centre for Minority Rights Development (CEMIRIDE), supported by the CGIAR, made a video with Kibet that has been shared widely on social media, in advocacy groups, and discussions on indigenous people’s rights across the country. His story brings much-needed attention to the plight of the Ogiek, highlighting injustice and the obstacles they face, alongside time-tested knowledge to address these challenges. Kibet’s journey gives us an insight into the transformative power of advocacy. Amongst those who have seen his video are judges from the Kenyan Environment and Land Court. His story has helped them recognize the importance of protecting the land rights of indigenous peoples, and the role they play in this process. When judges are confronted by cases of forced evictions brought on by commercial interests under the guise of conservation, a lack of understanding can lead to severe consequences for the indigenous people concerned.